Relasi Pengetahuan Islam Eksoteris dan Esoteris - Hammis Syafaq (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2012)
This article scrutinizes Islamic knowledge's relationship focusing on the esoteric realm and exoteric area or what so-called duality of life. Within intellectual treasures of Islam, this dualism has subsequently beaten each other. It is sometimes in the form of friction between the scientific and non-scientific, rational and spiritual, the sacred and the profane, theocentric and anthropocentric. However, when carefully understood, the dualism shares the same nature, namely the outer and inner aspects. The outer is represented by a name, while the inner can only be understood through the process of interpretation. These two aspects are represented by two words: name (outer aspect) and meaning (inner aspect). Therefore, Islam is present, and it attempts to draw both together. As can be observed in this century, the mentality of modern humans seems to be eroded far from religious norms as people have developed science, which leads to religious emptying from its noble values. Therefore, it is important to bring the esoteric realm into modern thought, which tends only to put emphasis on the exoteric aspect.